Taking a Chinese agricultural company public in the United States: The case of Yongye - Gilmore, Larry (My University, 2020)
The problem of interest in this research is providing insights into the difficulty perceived by Americans that foreign agricultural companies have little chance raising capital on Wall Street. The thesis narrates the path used by one Chinese firm to raise capital on the US stock market. The story is even more remarkable because Yongye is a Chinese company, unknown and inexperienced in the world of initial public offerings (IPO), yet made a bold entry into the US financial markets. The thesis tells that story from the author’s vantage point as a vice president in Yongye, and from the front row seat of all the negotiations leading to the successful IPO. The story focuses on the author’s personal experience working in Yongye as it sought to finance the company’s growth to support is vision to increase the prosperity of Chinese smallholder farmers. The company executes this vision within the context of China’s industrial expansion as well as its institutional structures. It also presents the product and technology which were the products that Yongye offered to the market. Yongye’s success in raising private and public funds in the US market from 2008 to 2010, came after overcoming many internal structural obstacles, and “lumpy” developments which existed in China’s agriculture sector. On a macro level, it is also juxtaposed against a planned economy driven forward by successive Five-Year Plans implemented by the communist government starting in 1953 and acceptance of the UN’s Millennial Development Goals implemented from 2000 to 2015. On a micro level, Chinese smallholder farmers found Yongye’s specialty fertilizer a compelling value as it helped them increase crop production and sell at higher prices which were in direct opposition to trends which saw arable land shrinking and becoming less productive due to over utilization. Ultimately, this story weaves together the description of how a SME agribusiness in China, through local entrepreneurship and foreign business expertise, was able to overcome major structural obstacles in China, and attract enough interest from foreign investors to finance its business and achieve company, national and UN goals. It provides insights into how small to medium size companies in any developing country, with the right product, a clear vision, and the tenacity of its leaders can procure the requisite financial resources to fund its growth. After all, capitalism is about opportunity to expand capital. Politics is only relevant if it becomes a barrier to the process of capitalism meeting its reason for existence.
Keywords: Youngye; Wall Street; SME agribusiness; China agriculture